Generación de energía eléctrica mediante el reaprovechamiento de biomasa (cáscara de papa y aguas residuales) por medio de bioceldas. 2016. - Carrasco Vergara, Angie Lisette (2018)
The objective of this research was to demonstrate that biomass (potato peel and wastewater) can be reused in the generation of electric energy by means of biocells to reduce uncontrollable increase of solid waste, excessive use of non-renewable energy and the consumption of electric energy as well as of fossil fuels. The procedure for the investigation was performed manually, first the amount of potato peel was determined, then the liquid was extracted from glucose to be used as a substrate. The residual water was then collected, and a portion of the sample was sent for analysis. Subsequently the construction of the biocelda was carried out following the design previously elaborated, of which the anodic chamber consisted of 357.76ml, the cathodic of 265.92ml. Finally, the experiment was started with different amounts of residual biomass and in this way the best of the treatments was found. The experimental part was carried out in a laboratory in the town of Carabayllo, Lima. For the anodic solution composition in Treatment 1, a) 35 ml of the liquid extracted from 100.21 g of potato peel, b) 250 ml of waste water (obtained from the potato washing process) and c) Bio culture material (Obtained from wastewater). For the cathodic solution of Treatment 1, a) 270 ml of distilled water (H2O), to which 2% Sodium Chloride (NaCl) was added, was used to increase the electrical conductivity. For treatments 2, 3 and 4 the amount of potato peel was varied, being 200, 300 and 400 grams respectively. From the results obtained in the investigation, the treatment No. 4 showed the maximum voltage, being 0.80 V, the current intensity of 0.1 A and generating a maximum power of 0.080 W, during the 7 days of experimentation.